Kajian Literatur tentang Penerapan Aplikasi GeoGebra dalam Pembelajaran Transformasi Geometri Siswa SLTA Sederajat - Mariana Mariana; Putri Khairani; Rahma Aulia (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study is a literature review that aims to identify and analyze the application of GeoGebra applications in learning geometric transformations at the high school level. Geometric transformation is a material that requires high spatial visualization skills, so learning media are needed that are able to present concepts in a concrete and interactive way. GeoGebra, as a dynamic mathematics application, is considered capable of facilitating student understanding through direct visualization of transformation processes such as translation, reflection, rotation, and dilation. The study was conducted by reviewing 11 relevant scientific articles, published in the last five to ten years, and meeting certain inclusion criteria. The results of the analysis show that the application of GeoGebra in learning has a positive impact, both cognitively, affectively, and technically. GeoGebra is able to improve students' understanding of concepts, learning motivation, and learning outcomes. The implementation strategy includes the development of e-modules, digital teaching materials, problem-based learning, and application usage training. Overall, GeoGebra has proven to be valid, practical, and effective in supporting more interesting and meaningful learning of geometric transformations.